2018
DOI: 10.1136/bmjgh-2018-000850
|View full text |Cite
|
Sign up to set email alerts
|

Production costs and potential prices for biosimilars of human insulin and insulin analogues

Abstract: IntroductionHigh prices for insulin pose a barrier to treatment for people living with diabetes, with an estimated 50% of 100 million patients needing insulin lacking reliable access. As insulin analogues replace regular human insulin (RHI) globally, their relative prices will become increasingly important. Three originator companies control 96% of the global insulin market, and few biosimilar insulins are available. We estimated the price reductions that could be achieved if numerous biosimilar manufacturers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 20 publications
0
44
0
1
Order By: Relevance
“…In late 2018, Gotham and colleagues21 conservatively estimated that manufacturers’ selling prices (covering production costs, profit, transport and other costs) should be $3.29 to $4.93 for biosimilar human insulin and $5.32 to $9.13 for most analogues. Our study found governments were paying far more, particularly for analogues (but also for human insulins in some countries), showing scope for price reductions while still providing a profit for the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…In late 2018, Gotham and colleagues21 conservatively estimated that manufacturers’ selling prices (covering production costs, profit, transport and other costs) should be $3.29 to $4.93 for biosimilar human insulin and $5.32 to $9.13 for most analogues. Our study found governments were paying far more, particularly for analogues (but also for human insulins in some countries), showing scope for price reductions while still providing a profit for the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, three companies -Novo Nordisk, Eli Lilly and Sanofi -control 96% of the global insulin market. 5 "Some prescribers may lack confidence in biosimilar manufacturers if they do not have a track record in insulin development," says Miles Fisher, Consultant Diabetologist, Glasgow Royal Infirmary. But the growing competition may challenge the current hegemony in the insulin market.…”
Section: Mark Greenermentioning
confidence: 99%
“…The FDA held a public hearing in May 2019 about the future of insulin biosimilars to discuss its regulatory process for biosimilar and interchangeable insulin products. We will have to see if any changes show up in the United States when this approval process for insulins will become active and what impact this will have on insulin prices (10,11).…”
Section: Biosimilar Insulinmentioning
confidence: 99%